2020
DOI: 10.3390/antiox9101016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bioactive Compounds, Antioxidant Activity, and Nutritional Quality of Blood Orange Cultivars at Different Storage Temperatures

Abstract: Information about the postharvest physiological behavior of blood orange cultivars can provide comprehensive insight into the best period of storage to maintain the highest fruit quality during prolonged cold storage. In this paper, changes in nutritional quality, bioactive compounds, and antioxidant enzymes in the juice of four blood orange cultivars (“Moro”, “Tarocco”, “Sanguinello”, and “Sanguine”) stored at 2 and 5 °C were studied. Parameters were measured after 0, 30, 60, 90, 120, 150, and 180 days, plus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 38 publications
2
36
0
5
Order By: Relevance
“…It seems that all of these conditions affected anthocyanins accumulation in control samples. In addition, chilling-inducing temperatures (≤5°C) cannot enhance anthocyanin accumulation as previously reported in untreated blood oranges fruit ( Carmona et al, 2017 ; Habibi et al, 2020a ). Therefore, treated fruit had an enhancement of anthocyanin accumulation during 42 days at cold temperature with a significant difference with control samples.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It seems that all of these conditions affected anthocyanins accumulation in control samples. In addition, chilling-inducing temperatures (≤5°C) cannot enhance anthocyanin accumulation as previously reported in untreated blood oranges fruit ( Carmona et al, 2017 ; Habibi et al, 2020a ). Therefore, treated fruit had an enhancement of anthocyanin accumulation during 42 days at cold temperature with a significant difference with control samples.…”
Section: Discussionsupporting
confidence: 72%
“…Anthocyanin accumulation depends on storage temperatures and cultivars ( Habibi et al, 2020a ). It has been reported that blood orange cultivars are cold dependent for the synthesis of anthocyanin after harvest, but enhancement of anthocyanin at moderate temperature was significantly higher than cold temperature and efficiency of colder temperature (below 3°C) was inefficient ( Habibi et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chilling injury observed on the rind is related to fruit quality and marketability of blood orange fruit. Our previous publication demonstrated that the tolerance cultivar had a higher quality than the susceptible cultivar as it did in 'Sanguinello' [38].…”
Section: Discussionmentioning
confidence: 91%
“…In fact, the cultivar, the cultivation method, the ripening degree, the harvest season and pre-harvest or postharvest chilling stresses can significantly affect the composition of plant tissues and, thus, their mechanical strength [141] and response to physical stresses induced by processing, with effects on the release and oxidation of polyphenols after freezing and thawing [22,73,142]. In particular, these variables influence the composition of plant foods by affecting (i) the content of proteins and of sugars, which act as natural cryoprotectants [143], (ii) the phenolic content and composition due to the shift of the pathways involved in their biosynthesis [139,[144][145][146] and the concentration of oxidase enzymes, such as polyphenoloxidase, whose activity is affected not only by the total polyphenol content but also by the content of single polyphenols and/or by their oxidation products [147]. ORAC: Oxygen Radical Absorbance Capacity; FRAP: Ferric Reducing Antioxidant Power; ABTS: 2,2 -azinobis (3-ethylbenzothiazoline-6-sulfonic acid) radical cation assay; DPPH: 2,2-diphenyl-1-picrylhydrazyl free radical assay; DR: deoxyribose degradation assay.…”
Section: Combined Effect Of Freezing and Frozen Storagementioning
confidence: 99%